Pengaruh Aktivitas Seksual Selama Kehamilan terhadap Kejadian Persalinan Preterm di RSU Kec. Obi, Halmahera Selatan - Sulastri La Taja; Widia Shofa Ilmiah (Lembaga Pengembangan Kinerja Dosen, 2025)
Preterm labor remains one of the leading challenges in maternal health due to its association with increased neonatal morbidity and mortality. Among behavioral factors suspected to contribute to early delivery, sexual activity during pregnancy may induce uterine stimulation and physiological changes in the cervix. This study aimed to examine the relationship between the frequency of sexual activity during pregnancy and the incidence of preterm birth. A cross-sectional quantitative approach was employed, involving 30 postpartum women who delivered at the Obi Subdistrict General Hospital, South Halmahera. Data were collected using structured questionnaires and medical records, then analyzed using the Spearman correlation test. The findings show that most respondents engaged in sexual activity 1–5 times during pregnancy, while a smaller portion reported six or more times. A total of 20% of participants experienced preterm delivery. The statistical analysis reveals a very strong relationship between sexual activity frequency and preterm birth, with a correlation coefficient of 0.894 and a p-value of 0.000. Frequent sexual activity during pregnancy tends to be associated with a higher incidence of preterm labor. These findings highlight the need for antenatal education to include accurate information about safe sexual practices during pregnancy, particularly for women with cervical vulnerability or a history of obstetric risk. Clear, evidence-based counseling can help couples make informed decisions and contribute to better pregnancy outcomes.